Developing Skills in Interpretative Guiding at Batuan Village, Gianyar, Bali - Koeswiryono, Dika Pranadwipa (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service initiative in Batuan Village, Gianyar, exemplifies a collaborative effort between Institut Pariwisata dan Bisnis Internasional (IPB Internasional) and the local community. The well-structured program aimed to empower Batuan Village residents by providing training to become proficient guides, enhancing the tourism experience. Divided into planning, implementation, and evaluation stages, the initiative involved a participatory approach, encouraging active engagement and practical learning. Through thoughtful site selection, material preparation, and live practice sessions, participants gained confidence and skills. The emphasis on impactful interpretation, and incorporating human emotions into narratives, elevated the quality of presentations. The success of the initiative is attributed to the support of IPB Internasional, the student organization, the Village of Batuan, and the enthusiastic local participants, showcasing the positive outcomes achievable through collaborative, community-driven initiatives for sustainable cultural heritage and tourism development.